Recognition of professional qualifications from learning online - Alfredo Soeiro (2014)
A methodology is proposed to address the recognition of competences acquired online. It is derived from the project VIRQUAL (http://virqual.up.pt) outputs. It addresses current issues of the working world like Virtual Mobility, Learning Outcomes, e-Assessment, Qualification Frameworks and Recognition of Prior Learning. The approach is based on the application of proper methods of assessment for each type of learning outcomes. A matrix is proposed to align the different types of competences (based on revised BloomŽs taxonomy) with the different types of assessment online. The involvement of professional stakeholders derives from the inclusion of the professional qualification frameworks in the choice of learning outcomes.